RFID event mining for MRO - based on association rules - Tan, Huei Chong. (2010)
The document is known as Final Report for Final Year Project (FYP) with project no. B4161-091: RFID Event Mining for MRO. All the research works in Data Mining are done in AY2009/2010 by NTU-EEE student Tan Huei Chong (072079J03), and will be described, illustrated, and explained in detail. The research done is based on the dynamic nature of the maintenance, repair and overhaul industry in aerospace. Due to the dynamic nature of the industry, the tracing and tracking of the equipments or parts involved become a critical part. With the technology of radiofrequency identification (RFID), the information needed for tracing and tracking process can be recorded in data. With large amount of data, the digging of useful information becomes a challenge. The data digging process is known as data mining (DM) or knowledge discovery. This project raises this challenge. The findings and researches done are illustrated in this report. The DM algorithms based on association rules are presented in one of the DM tools used in this project, by creating a prototype. The prototype is evaluated on its functionality and its limitations. Future works are recommended afterwards aiming at resolving the limitations.